Wild or Tamed? : India's Potential Growth - Oura, Hiroko (Washington, D.C. : International Monetary Fund, 2007)
With India's GDP expanding at a rate above 8 percent in recent years, the debate about whether India is overheating revolves mainly about whether growth is above potential-that is, whether the economy is exceeding its "speed limit." This paper attempts to shed light on this debate by providing up-to-date projections of India's potential growth, including by clarifying differences in underlying assumptions used by various researchers that lead to a range of estimates. Estimates of potential growth on this basis range from 7.4 percent to 8.1 percent for 2006/07, and about 8 percent for the medium term. The medium-term potential estimates have risks on both sides: productivity gains and investment could be volatile, but determined reforms could sustain strong productivity growth.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet